Multifunctional dendrimers for antibacterial applications - Leire, Eva Emma Maria (2016)
In this thesis gallic acid-triethylene glycol (GATG) dendrimers were synthesised and efficiently functionalized with hydroxyl groups, phenylboronic acids and primary amines. The interactions of the dendrimers with bacteria and the potential for development of new antimicrobials were evaluated in this study. Specifically, the ability of the dendrimers to induce bacterial clustering and interfere with small molecule autoinducer-2 (AI-2) in the Quorum Sensing (QS) pathway of the marine bacteria V. harveyi was studied with the use of Coulter Counter aggregation assays and detection of QS–controlled luminescence. Novel alkynylated ligands with diol-, tetraol-, glucose- and mannose- moieties were synthesised and successfully functionalized to GATG dendrimers of generation G1 and G3 through catalyst-free azide-alkyne cycloaddition (AAC). The results of luminescence experiments reveled that the dendrimers functionalized with hydroxyl groups decreased AI-2 induced luminescence of V. harveyi MM32 at the at early time points (4 h) while a dose-dependent increase of luminescence and increased bacterial growth was observed at later time points. GATG dendrimers of generation G1 and G3 were decorated with 9 and 81 phenylboronic acid in the periphery. These dendrimers had an inhibitory effect on growth and luminescence as observed by luminescence, aggregation and colony forming unit-counting assays. Although the mechanism is not yet fully understood, these promising results should be further explored. Cationic GATG dendrimers of generation G1, G2 and G3 with 9, 27 and 81 primary amines in the periphery induced formation of clusters in V. harveyi in a generation dependent manner, an improved ability to induce cluster formation when compared with poly(N-[2- (dimethylamino)propyl]methacrylamide), a cationic linear polymer previously shown to cluster bacteria. Viability of the bacteria within the formed clusters and the evaluation of the QS controlled luminescence suggests that the GATG dendrimers may be activating microbial responses by maintaining a high concentration of QS signals inside the clusters while increasing permeability of the microbial outer membrane. Thus, a generation-dependent effect in bacterial luminescence production and membrane permeability was induced by the cationic dendrimers. The inhibition of growth and increased membrane permeability in combination with cell clustering may be promising antibacterial features of these dendrimers. These results highlight the potential of the GATG dendritic platform to develop new antimicrobials aimed to target microbial viability and/or virulence (e.g. adhesion) and encourage further investigations on the importance of polymeric architecture and multivalency in the antimicrobial field.